2012
DOI: 10.1111/j.1460-9568.2012.08183.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of a sex pheromone receptor in the pest moth Spodoptera littoralis by heterologous expression in Drosophila

Abstract: Moth sex pheromone communication is recognised as a long-standing model for insect olfaction studies, and a widespread knowledge has been accumulated on this subject thanks to numerous chemical, electrophysiological and behavioural studies. A key step has been the identification of candidate sex pheromone receptors, opening new routes to understanding the specificity and sensitivity of this communication system, but only few of these receptors have as yet been functionally characterised. In this context, we ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 47 publications
3
89
0
1
Order By: Relevance
“…CpomOR3 was almost equally sensitive when expressed in trichoid T1 and basiconic ab3 sensilla, except at the highest dose of pear ester (Figure 4). Interestingly, the pheromone receptors BmorOR1 of silkmoth B. mori and SlitOR6 of cotton leafworm moth S. littoralis were more sensitive when expressed in T1 than in ab3 sensilla (Syed et al, 2010;Montagné et al, 2012). This indicates that T1 sensilla, containing an important PR partner, the sensory neuron membrane protein (Benton et al, 2007), are more adapted for correct PR functioning, whereas plant odorant ORs function equally well in T1 or ab3.…”
Section: Cpomor3 Belongs To the Pheromone Receptor Cladementioning
confidence: 75%
See 3 more Smart Citations
“…CpomOR3 was almost equally sensitive when expressed in trichoid T1 and basiconic ab3 sensilla, except at the highest dose of pear ester (Figure 4). Interestingly, the pheromone receptors BmorOR1 of silkmoth B. mori and SlitOR6 of cotton leafworm moth S. littoralis were more sensitive when expressed in T1 than in ab3 sensilla (Syed et al, 2010;Montagné et al, 2012). This indicates that T1 sensilla, containing an important PR partner, the sensory neuron membrane protein (Benton et al, 2007), are more adapted for correct PR functioning, whereas plant odorant ORs function equally well in T1 or ab3.…”
Section: Cpomor3 Belongs To the Pheromone Receptor Cladementioning
confidence: 75%
“…Amino acid sequences of CpomORs clustering in the candidate PR clade (Bengtsson et al, 2012) were included in a dataset together with sequences of candidate PRs from the following Lepidoptera: Antheraea polyphemus (Forstner et al, 2009), Bombyx mori (Nakagawa et al, 2005), Danaus plexippus (Zhan et al, 2011), Diaphania indica (Mitsuno et al, 2008), Epiphyas postvittana (Jordan et al, 2009), Heliconius melpomene (Heliconius Genome Consortium, 2012), Helicoverpa armigera (Liu et al, 2012), Heliothis virescens (Grosse-Wilde et al, 2007;Wang et al, 2010), Manduca sexta (Grosse-Wilde et al, 2010), Mythimna separata (Mitsuno et al, 2008), Ostrinia furnacalis (Miura et al, 2010;Leary et al, 2012), O. nubilalis (Wanner et al, 2010;Leary et al, 2012), O. scapulalis (Miura et al, 2009(Miura et al, , 2010, Plutella xylostella (Mitsuno et al, 2008;Sun et al, 2013), Spodoptera exigua and S. littoralis (Legeai et al, 2011;Montagné et al, 2012). Sequences from B. mori (BmorOR6) and H. melpomene (HmelOR5, 6, and 7) were also included in the dataset as external groups, since they belong to the sister group to the PR clade (Poivet et al, 2013).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…A number of lepidopteran OR gene repertoires have been described, following genome and transcriptome sequencing (Jordan et al, 2009;Grosse-Wilde et al, 2011;Montagné et al, 2012Montagné et al, , 2014Cao et al, 2014;Gu et al, 2014;Liu et al, 2014;Corcoran et al, 2015;Yang et al, 2015;Zhang et al, 2015a,b). In our own transcriptome sequence analyses of the antennae of the codling moth (Cydia pomonella: Tortricidae; Bengtsson et al, 2012) and the cotton leafworm (Spodoptera littoralis: Noctuidae; Legeai et al, 2011;Jacquin-Joly et al, 2012;Poivet et al, 2013) we have identified one OR (OR19) with relatively high sequence similarity in both species.…”
Section: Introductionmentioning
confidence: 99%